Conflicting Identities: Cosmopolitan or Anxious? Appreciating Concerns of Host Country Population Improves Attitudes Towards Immigrants - Tobias Stöhr; Philipp Wichardt (Institute of Labor Economics (IZA), 2019)
This paper connects insights from the literature on cosmopolitan values in political science, anxiety in social psychology, and identity economics in a vignette-style experiment. We asked German respondents about their attitudes towards a Syrian refugee, randomizing components of his description (N=662). The main treatment describes the refugee as being aware of and empathetic towards potential Germans' worries about cultural change, costs and violence associated with refugee inflows. This increases reported levels of sympathy and trust substantially, especially for risk averse people. We argue that acknowledging concerns of the host population relieves the tension between an anxious and a cosmopolitan part of peoples' identities. When one aspect of identity is already acknowledged (expressing anxieties) it has less influence on actual behavior (expressing sympathy). In addition, we find that previous contact with foreigners and a higher willingness to take risks are important factors to determine an individual's willingness to interact with refugees.
Keywords: F22; Z10; Z12; 330; identity; integration; attitudes; immigration; refugees